The Linguistics of Lying And Other Essays - Weinrich, Harald (Book collections on Project MUSE., 2005)
"Weinrich brings sophisticated thinking about semantics to bear on the question of how, and how much, language corresponds to thought. His survey of the different ways in which language is untrue forges striking links between linguistic and literary categories on the one hand and ethics and even good manners on the other. Now, with a translation that captures the wide appeal of the original texts, Jane and Marshall Brown have opened a path to the broader recognition among English readers that Weinrich's work so richly deserves."--Jacket